2011
DOI: 10.1515/jaots-2011-0208
|View full text |Cite
|
Sign up to set email alerts
|

Maleic Acid Oxidation Using A Heterogeneous Modified Polyacrylonitrile (PAN) Fibrous Catalyst

Abstract: The effectiveness, kinetics and mechanism of oxidation of maleic acid in solution using a novel modified polyacrylonitrile (PAN) catalyst/hydrogen peroxide system was studied. The modified PAN catalyst contains immobilised Fe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This suggests that 30%-40% of organic compounds present in the wastewater were mineralised to produce CO 2 and water. Although TOC removal is somewhat low, the oxidation of these organic pollutants generally results in the formation of low molecular weight organic acids that are readily biodegradable [18] but which results in no change in TOC. It is has been widely reported that the oxidation of PPCP and steroid hormones by hydroxyl radicals results in loss of estrogenicity [14].…”
Section: Removal Of Bod Toc Tssmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that 30%-40% of organic compounds present in the wastewater were mineralised to produce CO 2 and water. Although TOC removal is somewhat low, the oxidation of these organic pollutants generally results in the formation of low molecular weight organic acids that are readily biodegradable [18] but which results in no change in TOC. It is has been widely reported that the oxidation of PPCP and steroid hormones by hydroxyl radicals results in loss of estrogenicity [14].…”
Section: Removal Of Bod Toc Tssmentioning
confidence: 99%
“…The heterogeneous polyacrylonitrile (PAN) catalyst/ H 2 O 2 has shown potential at lab scale in the treatment of synthetic organic contaminants [17][18][19]. This study aims to examine the effectives of the heterogeneous PAN catalyst/H 2 O 2 at a pilot scale, towards the removal of selected EDCs and PPCPs from pretreated (activated sludge treated) municipal wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…One of the materials successfully used is a surface functionalised nanocoated modied polyacrylonitrile (MPAN) bre in the form of a mesh. [3][4][5][6] The PAN mesh was modied to introduce surface functionalisation by amidoximation with a mixture of hydrazine and hydroxylamine at alkaline pH to allow surface complexation with iron(III) sulphate salt. 3,[7][8][9] This introduces groups such as amidoxime, amidrazone, amide and carboxylate onto the bres of the PAN mesh.…”
Section: Introductionmentioning
confidence: 99%
“…3,[7][8][9] This introduces groups such as amidoxime, amidrazone, amide and carboxylate onto the bres of the PAN mesh. 5 An Extended X-ray Absorption Fine Structure (EXAFS) study showed that the iron is surrounded by six atoms which are either O, or N or a mixture of both. When used with hydrogen peroxide at pH 3, the catalyst is seen to give excellent oxidation of organic pollutants in wastewater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation